2010
DOI: 10.2478/v10042-010-0034-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of CA 19-9 level in resectable pancreatic adenocarcinoma.

Abstract: Abstract:The prognosis in patients with pancreatic cancer is poor and some authors describe it as a lethal disease. At the time of diagnosis only 14% of patients could be surgically treated and up to 30% of them die within 12 months. Therefore, further clinical investigations on preoperative patient qualification are needed. A total of 81 patients were included into the study. The CA 19-9 concentration was measured before surgery by an automated, commercially available enzyme immunoassay in Axsym analyzer (Abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…Sensitivity is the ability of the test to detect disease. CA 19-9 has been shown to have a specificity of approximately 85% and a sensitivity of 90% [15, 17]. In our study, the sensitivity is 88%.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Sensitivity is the ability of the test to detect disease. CA 19-9 has been shown to have a specificity of approximately 85% and a sensitivity of 90% [15, 17]. In our study, the sensitivity is 88%.…”
Section: Discussionsupporting
confidence: 47%
“…Currently, the best known and examined pancreatic cancer marker is CA 19-9. The characteristics of an ideal marker are high sensitivity, high specificity, predictive value and specificity of the organ [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also indicated that elevated serum CA19-9 levels are associated with aggressive tumor behavior, such as larger tumor size, lymph node metastasis, peritoneal in ltration, and liver metastasis. 19 For CA242, some studies have found through immunohistochemistry as well as biochemistry that CA242 is most likely a product of tumor cells, so high levels of CA242 are associated with increased tumor burden. 14 It has also been shown that CA242 levels are elevated in patients with advanced pancreatic cancer, which strongly predicts that elevated preoperative CA242 levels are strongly associated with metastatic and aggressive behavior of the tumor and can present a very poor prognosis for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is the only blood test approved by the Food and Drug Administration (FDA) for pancreatic adenocarcinoma. CA 19–9 has demonstrated specificity of approximately 85% and sensitivity of 90% [ 9 , 10 ], and its prognostic value for survival is more associated with high postoperative dosage [ 11 ].…”
Section: Discussionmentioning
confidence: 99%